The folk-medicinal plants of Kadisehri (Yozgat - Turkey) - EMRE, GİZEM (POLSKIE TOWARZYSTWO BOTANICZNE, 2015)
This paper contains significant ethnobotanical information on folk-medicinal plants and their ethnopharmacological uses in Kadisehri. The aim of the study was mainly to collect and identify the plants used therapeutically by the local people, and to make available information about traditional herbal medicine. It was undertaken during the period 2011-2012 and is based on plants collected during field work. Fifty-six plants used in folk-medicine and belonging to 34 families were identified in this study. Of these, 48 species were wild, and 8 species were cultivated plants. The most common families were Rosaceae (12.5%), Lamiaceae (8.9%) and Asteraceae (7.1%); and the most common preparations were decoctions (36.7%). In addition, a cultural importance index (CI) and use report (UR) were calculated for each species. Based on the CI, the most important plants were Cydonia oblonga (0.77), Ecballium elaterium (0.66), Urtica urens (0.66), Vitis vinifera (0.66), Plantago lanceolata (0.65), Plantago major subsp. major (0.65) and Rosa canina (0.62). We found three species of plant (Astragalus noaeanus, Populus xcanescens and Salvia cyanescens) which had never before been reported to have medicinal properties.
Keywords: ethnobotany; traditional medicine; Kadisehri; Yozgat; Turkey; TRADITIONAL MEDICINE; ETHNOBOTANICAL SURVEY; WILD PLANTS; ANTIMICROBIAL ACTIVITIES; ANKARA PROVINCE; EAST ANATOLIA; WEST ANATOLIA; PART; DISTRICT; PURPOSE